Pengaruh Model Pembelajaran Literasi, Orientasi, Kolaborasi dan Refleksi (LOK-R) Berbantuan Ice Breaking terhadap Kemampuan Membaca Siswa Kelas IV di SD YPK 1 Efata Serui - Lirhan Lirhan; Nurwafiat Hamka (Lembag, 2024)
The main objective of this research is to determine the effect of the Literacy, Orientation, Collaboration, and Reflection (LOK-R) learning model aided by Ice Breaking on the reading ability of fourth-grade students at SD YPK 1 Efata Serui. The type of research is quasi-experimental design. The population of this study is all 172 students at SD YPK 1 Efata Serui, while the research sample consists of 29 fourth-grade students. Data collection was carried out through reading ability tests, observation sheets, and documentation. The collected data was analyzed using inferential statistical techniques. Based on the data analysis, the average score in the experimental class before treatment was 55.5, while after treatment it was 88.5. In the control class, which used direct instructional model, the average pretest score was 60.5 and the post-test score was 67.5. Hypothesis testing for the experimental class yielded a normal gain test of 0.68, which means it was very effective, while the control class obtained a normal gain test of 0.29, indicating that it was not effective. Based on the research results, it can be concluded that there is an influence of the Literacy, Orientation, Collaboration, and Reflection (LOK-R) learning model aided by Ice Breaking on the reading ability of fourth-grade students at SD YPK 1 Efata Serui.